PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT DALAM MEMODERASI HUBUNGAN PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT (ERM) TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2016- 2020) - Aulia Rahma Adissa; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
This study aims to obtain empirical evidence and analyze the effect of sustainability reporting disclosures in moderating the relationship between Enterprise Risk Management (ERM) disclosures on company performance.             The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the period 2016-2020. Meanwhile, there were 67 research samples used based on predetermined criteria.            Data analysis was performed by descriptive statistical analysis, classical assumption test, and hypothesis testing. The results of the analysis of the study indicate that the disclosure of Enterprise Risk Management (ERM) has a positive and significant effect on company performance. In addition, the sustainability report can moderate the relationship of Enterprise Risk Management (ERM) disclosure to company performance.